Studies On Mycobacteriosis In Siamese Fighting Fish Betta Splendens Regan - Pungkachonboon, Temdoung (1994)

(untitled)
Siamese fighting fish, Betta splendens Regan mortalities in Thailand are usually associated with mycobacteriosis. The present study was undertaken to isolate and characterise mycobacteria from Siamese fighting fish, examine their sensitivity to selected antibiotics and to test the efficacy of kanamycin sulphate as a chemotherapeutic agent against mycobacteria. Histopathological studies on the Siamese fighting fish, experimentally and naturally infected with mycobacteria, were also conducted.Ten acid-fast, rapidly growing, photochromogenic strains of mycobacteria were isolated from apparently healthy fish and fish showing gross lesions of mycobacteriosis. Prevalence of mycobacteria in farm reared Siamese fighting fish ranged from 0-8%. Primary isolation of mycobacteria were successful on Ogawa egg medium and Lowenstein Jensen medium. The isolates grew within 5-7 days at 28°C on Ogawa egg medium and showed a temperature preference of 15- 17 °C. No growth was observed at 42°C. Optimum incubation temperature was 30°C. They were considered as mesophyllic forms. The organism produced mycolic acid which melted between 50.5-7 0°C. On the basis of their biochemical and physiological properties and the percentage guanine plus cytosine, the pathogen was confirmed as Mycobacterium sp. and was analogous to " M . piscicida " with similarity of 94% , but differed from the reference strains M. chelonae sub sp. chelonae , M . fortuitum , M . marinum , M . parafortuitum and M . vaccae by many characteristics. An antibiotic sensitivity test was conducted using seventeen antimicrobial agents against ten mycobacteria strains isolated from Siamese fighting fish. Kanamycin at 30 ug was the most effective antibiotic against mycobacteria. MIC and MBC values of kanamycin sulphate were 6 .25-12.50 and 12.5-25.0 ppm, respectively. However, treatment of mycobacteriosis with kanamycin, in vivo , was unsuccessful.